Topical Delivery of Mesenchymal Stem Cells “Secretomes” in Wound Repair - Indah Julianto; Yuyun Rindastuti (Acta Medica Indonesiana)
Wound healing requires a coordinated interplay among cells, growth factors, and extracellular matrix proteins. Central to this process is the endogenous mesenchymal stem cell (MSC), which coordinates the repair response by recruiting other host cells and secreting growth factors and matrix proteins. MSCs are self-renewing multipotent stem cells that can differentiate into various lineages of mesenchymal origin such as bone, cartilage, tendon, and fat. In addition to multilineage differentiation capacity, MSCs regulate immune response and inflammation and possess powerful tissue protective and reparative mechanisms, making these cells attractive for treatment of different diseases. The beneficial effect of exogenous MSCs on wound healing was observed in a variety of animal models and in reported clinical cases. Specifically, they have been successfully used to treat chronic wounds and stimulate stalled healing processes. Recent studies revealed that human placental membranes are a rich source of MSCs for tissue regeneration and repair. This review provides a concise summary of current knowledge of biological properties of MSCs and describes the use of MSCs for wound healing. In particular, the scope of this review focuses on the role MSCs have in each phase of the wound-healing process, and clinical reports transplatation MSCs – secretomes in chronical ulcer.